Ropivacaine induces neurotoxicity by activating MAPK/p38 signal to upregulate Fas expression in neurogliocyte. (27th July 2019) - Wang, Shuai; Lin, Quan; Wang, Zhengjie; Pan, Xiaolei
Highlights: Ropivacaine induces neurogliocyte apoptosis. Ropivacaine increases the expression of Fas to induce apoptosis. Ropivacaine-induced MAPK/p38 signal activation contributes to the neurotoxicity of neurogliocyte. Abstract: It has been recognized that the use of ropivacaine may cause neurotoxicity and cardiotoxicity in the perioperative period of local anesthesia effects. However, the molecular mechanism of ropivacaine in causing the neurotoxicity remains unclear. Cell viability and cell apoptosis were assessed. The functions of mitochondria and mitochondria-dependent intrinsic apoptosis were also detected. The molecular mechanism of ropivacaine-caused neurotoxicity was also evaluated. We demonstrated that ropivacaine dose-dependently suppressed the viability of neurogliocytes, and promoted neurogliocytes apoptosis. Moreover, ropivacaine significantly increased the expression of Fas by promoting the phosphorylation of p38. Ropivacaine-induced upregulation of Fas activated mitochondria-dependent intrinsic apoptosis, including the decrease of the mitochondria membrane potential, opening the mitochondrial permeability transition pore, releasing cytochrome c, and translocating Bcl-2 family members. Knockdown of Fas significantly suppressed the ropivacaine-induced apoptosis. Furthermore, knockdown of p38 or p38 inhibitor remarkably decreased the expression of Fas and attenuated ropivacaine-induced cell apoptosis, indicating that activation of the MAPK/p38/Fas signal contributed to the ropivacaine-caused neurotoxicity. Our study supplies the evidence supporting the molecular mechanism by which ropivacaine activates the MAPK/p38/Fas signal to promote neurogliocyte apoptosis and suggests that the combination of p38 inhibitor with ropivacaine might be an effective strategy to decrease the ropivacaine-caused neurogliotoxicity.